Contributing Factors and Conversion Prevalence of Laparoscopic Cholecystectomy to Open Surgery - Faruquzzaman (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Back ground: The application of laparoscopic technique for cholecystectomy is expanding very rapidly and now performed in almost all major cities and tertiary level hospitals in our country. The laparoscopic approach brings numerous advantages at the expense of a new set of diffi culties leads to open conversion especially in training facilities. Objective: To determine the rate and associated causative factors of conversion to open cholecystectomy in case of laparoscopic cholecystectomy in our surgical practice. Methodology: 364 & 387 patients of laparoscopic cholecystectomy in BIRDEM General Hospital, Dhaka, Bangladesh and Khulna Medical College Hospital, Bangladesh were included in this prospective study on the basis of convenient purposive sampling from a period of 30.06.14 to 30.09.16 & 01.01.11 to 30.09.16 respectively. Result: Among the patients of BIRDEM, 25.5% cases were male and 74.5% patients were female. Mean±SD of age were 43±1.4 and 42±1.7 respectively, whereas among the KMCH patients, 26.1% were male and 73.9% were female. Mean±SD of age were 46±1.3 and 43±1.9 respectively. Among the total  64 cases in BIRDEM, in case of 277 (76.1% approximately), laparoscopic cholecystectomy was done due to  chronic cholecystitis whereas in case of KMCH it was 83.2%. The overall conversion rates were 5.2% in BIRDEM and 7.0% in KMCH. Diffi culties to defi ne the anatomy of Calot's triangle is the most important reason for open conversion which were 42.1% and 33.3% in the respective groups. Other important  causes were suspicion of CBD injury, bowel injury, cystic artery bleeding, bile duct injury and suspicion of gall bladder cancer. The prevalence rates are relatively higher in male sex, age ≥60 years, in presence of comorbidities, upper abdominal surgery, acute cholecystitis, history of jaundice, obesity, thickened gall bladder wall on ultrasound and preoperative ERCP which are approximately 8.6%, 9.1%, 6.4%, 9.1%,  8.1%, 9.5%, 8.2%, 7.6% & 7.7% respectively in BIRDEM, whereas these were 8.9%, 7.7%, 7.5%, 10.5%, 0.8%, 9.7%, 9.2%, 8.4% & 9.7% respectively in KMCH. Conclusion: An appreciation for these predictors of conversion will allow appropriate planning and patient selection by the operating surgeon.